Examining the legitimacy of inclusive innovation processes: perspectives from smallholder farmers in Uasin Gishu, Kenya - Opola, Felix Ouko; Klerkx, Laurens; Leeuwis, C.; Kilelu, C.W. (Informa UK Limited, 2023)
In recent decades, the concept of inclusive innovation has been used to refer to how innovation can include actors that are considered marginalised from its processes and outcomes. Contrary to the ‘expert-driven’ approaches prevalent in evaluating the legitimacy of such processes, this paper examines the legitimacy of inclusive innovation from the perspective of smallholder farmers with little resource endowments in Uasin Gishu, Kenya, that are targeted with various agricultural innovation interventions. Findings indicate that procedural aspects of legitimacy, such as including farmers as co-innovators and including their knowledge and skills in agricultural innovation processes, are an important criterion used by targeted farmers to accord legitimacy to such interventions. We also find that such interventions need to be stable over time to be legitimate to the intended beneficiaries. These criteria used by targeted actors can be an important addition to evaluation procedures and methods for inclusive innovation.